Safety evaluation of the food enzyme β‐glucosidase from the non‐genetically modified Penicillium guanacastense strain AE‐GLY - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Vittorio Silano; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Claude Lambré; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; et al. (EFSA Journal)
Abstract The food enzyme β‐glucosidase (β‐D‐glucoside glucohydrolase; EC 3.2.1.21) is produced with the non‐genetically modified Penicillium guanacastense strain AE‐GLY by Amano Enzyme Inc. The food enzyme is intended to be used in four food manufacturing processes. Dietary exposure to the food enzyme‐total organic solids (TOS) was estimated to be up to 4.054 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not raise a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 943 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 233. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that the risk of allergic reactions by dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.